Australian banks' approaches to privacy in an online world. (22nd March 2007) - Cranitch, Greg; Nguyen, Duc-Tho; Nguyen, Anne
Worldwide there have been many instances where access to the personal and financial information of private individuals was gained by unauthorised personnel. To protect such information, in Australia, national privacy principles, which are embodied in legislation, specify how private-sector organisations should handle any personal information that they collect. In this study, the privacy policies of 18 Australian banks, as published on their own websites, are assessed against these principles. While the results are fairly reassuring from the bank customers' viewpoint, some areas of concern do remain, and these have important implications for providers, consumers, and regulators of e-finance services.